Efficient pulse compression favourable thermal excitation scheme for non‐destructive testing using infrared thermography: a numerical study. Issue 19 (28th July 2020) - Siddiqui, J.A.; Patil, S.; Chouhan, S.S.; Wuriti, S.; Arora, V.; Mulaveesala, R.
Abstract : Active thermal non‐destructive testing (TNDT) has emerged as a swift, robust and cost‐effective non‐contact inspection method used to detect the surface and sub‐surface defects present in a wide verity of solid materials. To further increase the efficacy of the process, various pulse‐compression‐based post‐processing techniques are in use. However, the applicability of pulse compression‐based thermographic methods has limited due to the presence of side lobes that degrades the energy concentration capabilities within the main lobe. In order to address this limitation, this work proposes a poly‐phase code (P4‐code). P4 codes are very efficient and robust in the reduction of distribution of energy in side lobes by concentrating on the main lobe. This Letter proposes a numerical study on the applicability of P4 codes‐based pulse compression favourable thermal wave imaging approach for TNDT for testing and evaluation of steel specimen for identification of flat‐bottom hole defects located at different depths. Further performance of the proposed method is compared with the widely used linear frequency modulated thermal wave imaging by considering the signal‐to‐noise ratio as a figure‐of‐merit.